Trends in the Development of Long-Term Care in Selected European Countries - Suchecka, Jadwiga; Urbaniak, Bogusława (Olsztyn Economic Journal, 2018)
This paper is devoted to the analysis of the relationships between the level of development of long-term care (LTC) support for the elderly in selected European countries and public expenditure on long-term care, the health condition of the population and the scale of labor market flexibility in connection with a need to provide home care for dependents by working family members (informal carers). For this purpose, one performed a multidimensional analysis of the relationship and showed spatial similarities, creating their own rankings.